Optical FBG sensors for static structural health monitoring - Antunes, P. (2012)
In this paper, the monitoring of an adobe structure with optical fiber sensors is reported. Static measurements were made during a destructive test on a full-scale wall, in which an in-plane cyclic force was imposed by a hydraulic jack until its collapse. The recorded data with these sensors and the force applied evolution allows to identify the two instants when the major diagonal cracks occur in the wall. Initially, before the cracking, a linear elastic response was observed, corresponding to a deformation at each monitoring point proportional to the applied lateral force, being quantified the relation between the external force and the deformation at each point. This structural test allows demonstrating the feasibility of applying static optical FBG sensors to study the behavior and performance of civil engineering infrastructures even for extreme loading events.